2015
DOI: 10.1186/s13620-015-0039-0
|View full text |Cite
|
Sign up to set email alerts
|

Foot lesions in lame cows on 10 dairy farms in Ireland

Abstract: BackgroundLittle is known about foot lesions in dairy cattle in Ireland, managed under a pasture based system with housing during the winter and grazing for the rest of the year. Ten Irish dairy herds, with a lameness prevalence ranging from 9 to 17 % were locomotion scored routinely during the 2013 grazing season. Lame cows were foot trimmed and foot lesions recorded.Findings11.8 % and 89.6 % of cows had lesions recorded on front and hind feet respectively. No lesions were found in 6.9 % of cows. Sole haemorr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
23
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 19 publications
8
23
1
Order By: Relevance
“…Foot disorders observed were mainly localized on the hind feet (73.8 %) and less frequently on the front feet (26.2 %), confirming similar results recently described by Somers and O’Grady [ 25 ] for dairy cows, where 11.8 and 89.6 % of the cows showed lesions recorded on front and hind feet, respectively.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Foot disorders observed were mainly localized on the hind feet (73.8 %) and less frequently on the front feet (26.2 %), confirming similar results recently described by Somers and O’Grady [ 25 ] for dairy cows, where 11.8 and 89.6 % of the cows showed lesions recorded on front and hind feet, respectively.…”
Section: Discussionsupporting
confidence: 89%
“…White line disorders are considered some of the most important causes of severe lameness in cows [ 32 ]. While 4.8 % of the MB with FDs showed signs of WLA (Table 2 ), the values observed were lower than those recently described for lame cows, where the prevalence of WLA ranged from 17.2 to 23.5 % [ 25 , 32 ].…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Therefore, we recommend that on infected farms, New Zealand dairy farmers should undertake on-going monitoring of DD to assess the progress of the disease. Ideally, monitoring should occur multiple times during the season as part of routine foot health and lameness assessments [32]. However, if farmers can only conduct DD monitoring at a single time point, the model results suggest that late November to end of February would perhaps be the optimal time as the DD prevalence is likely to reach its peak during this period.…”
Section: Discussionmentioning
confidence: 99%
“…Most recent studies on lameness showed very different statistics. In Irish dairy herds the lameness prevalence ranged from 9-17% (Somers and O'Grady 2015). In the UK, the estimated prevalence of lame and severely lame cows was 36.8% (Barker et al 2010).…”
Section: Discussionmentioning
confidence: 99%